Preliminary clinical evaluation of traditional and a new digital PEEK occlusal splints for the management of sleep bruxism. (28th October 2020) - Wang, Shimin; Li, Zheng; Ye, Hongqiang; Zhao, Wenyan; Liu, Yunsong; Zhou, Yongsheng
Summary: Objective: To compare the manual time and preliminary clinical effects between the digital manufactured occlusal splints for sleep bruxism patients with those of traditional hard splints. Methods: Sixteen individuals (18 to 44 y/o) with clinically diagnosed sleep bruxism were selected based on the inclusion criteria. All patients were divided into two groups, and a random control method was applied. Digital splints (test group) were designed and milled using CAD/CAM. Hard splints (control group) were made of transparent acrylic resin in laboratory office. The manual time spent including impression obtaining, splint production and clinical occlusal adjustment was recorded. A visual analog scale was used to report the subjective evaluations. The maximum depth loss and volumetric loss of the occlusal surface of splints in posterior tooth were measured. SPSS software was used for statistical analysis ( P = .05). Results: Comparing with control group, the manual time spent in test group was significantly less in all of three procedures ( P < .001). The VAS scores for retention were not significantly different ( P = .086), but the wearing comfort scores of test group were significantly higher ( P < .001). Both maximum depth loss ( P = .007) and volumetric loss in test group were significantly less than control group ( P = .005). Conclusion: In the current study, the digitally manufactured splints exhibit significantly improved comfort and time efficiency than traditional hard splints. Moreover, the new milling material (PEEK) has better wear resistance than acrylic resins.